Effect of Tax Avoidance and Company Complexity on Firm Value: The Role of Transparency as a Moderating Variable - Suryani, Thalia Millene; Lastiningsih, Noegrahini; Wibawaningsih, Ekawati Jati (Journal of Economics and Behavioral Studies, 2021)
This study aims to analyze the effect of tax avoidance and company complexity on firm value with information transparency as a moderating variable so that internal and external parties can evaluate management performance to increase firm value positively. In this study, panel data regression and Moderated Regression Analyst (MRA) were carried out on 78 public manufacturing companies on the IDX during the 2017-2019 period. Tax avoidance is measured by the BTD proxy, the level of complexity is measured by the number of business segments, firm value is measured by Tobin’s q proxy, and information transparency is measured by the transparency index released by BAPEPAM. The results show that tax avoidance has a significant negative effect on firm value and firm complexity does not have a significant effect on firm value, while information transparency moderates the relationship between tax avoidance and firm value but is unable to moderate the effect of firm complexity on firm value.